Adverse Events Associated with Nirmatrelvir/Ritonavir: A Pharmacovigilance Analysis Based on FAERS - Meng Li; Qing-Song Zhang; Xin-Ling Liu; Hui-Ling Wang; Wei Liu (MDPI AG, 2022)
Nirmatrelvir/ritonavir is approved for the treatment of adults and pediatric patients with mild to moderate COVID-19, but information on adverse events associated with its use is limited. We aim to evaluate adverse events with potential risk for nirmatrelvir/ritonavir using the FDA Adverse Event Reporting System (FAERS). Disproportionality analysis was performed using the reporting odds ratio (ROR) method, and subset analysis based on patient age and gender, as well as sensitivity analysis restricting the type of reporter to healthcare professionals. Nirmatrelvir/ritonavir was the most commonly reported COVID-19 drug, and 87.66% of the outcomes were non-serious. The most frequently reported events were disease recurrence (40.43%), dysgeusia (17.55%), and diarrhea (8.80%). In disproportionality analysis, the use of nirmatrelvir/ritonavir was significantly associated with disease recurrence (ROR: 212.01, 95% CI: 162.85-276.01), whereas no signal of disease recurrence was detected for any other COVID-19 drug. Disease recurrence (ROR: 421.38, 95% CI: 273.60-648.99) was more significant when limiting the reporter type to healthcare professionals. No significant differences in adverse event reports were found based on patient gender or age. Our study confirms that the risk of serious adverse events is low with nirmatrelvir/ritonavir, but its association with disease recurrence should not be ignored.